Archaeological Research of the "Karmir (Red) Church" in Tsovataq Village - Safaryan, Vardges (History and Culture, 2025)
After the 2020 Artsakh 44-day war, a vast number of monuments remained under Azerbaijani control. Archaeological studies continued in the parts of Artsakh Republic that remained under its control during 2021-2022.This article presents the main results of the archaeological research conducted in the area of the "Karmir (Red)Church" in Tsovataq village, Martuni district, Artsakh Republic.The excavations revealed that the "Karmir (Red) Church" is a single-nave, vaulted hall with a semi-circular apse, constructed with rough-hewn stones.
Keywords: "Karmir (Red) Church"; Artsakh; Bishop Davit; Melik Pashayan; Sargis Jalalyants; Tsovataq